2016
DOI: 10.1021/acs.nanolett.5b04724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Adsorption on Carrier Trapping Dynamics at the Surface of Anatase TiO2 Nanoparticles

Abstract: Charge carrier trapping plays a vital role in heterogeneous photocatalytic water splitting because it strongly affects the dynamics of photogenerated charges and hence the photoconversion efficiency. Although hole trapping by water at water/photocatalyst interface is the first step of oxygen evolution in water splitting, little has been known on how water adsorbate itself is involved in hole trapping dynamics. To clarify this point, we have performed infrared transient and steady-state absorption spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 29 publications
4
72
0
Order By: Relevance
“…The relative amounts of surface OH groups were normalized to Degussa P25 as follows: Degussa:ST-01:AHP-ST-01 = 1:1.9:3.2, listed in Table 1. However, it should be noted that the water adsorbates observed under the vacuum were very strongly bound through oxygen of water to a less coordinated Ti cation and a hydrogen bond to a surface oxygen atom [8]. In the FTIR study of ST-01 at 0.01 Pa, 80% of the intensity of the OH stretching band at room temperature was contributed by molecularly adsorbed water, while only 20% was by surface OH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative amounts of surface OH groups were normalized to Degussa P25 as follows: Degussa:ST-01:AHP-ST-01 = 1:1.9:3.2, listed in Table 1. However, it should be noted that the water adsorbates observed under the vacuum were very strongly bound through oxygen of water to a less coordinated Ti cation and a hydrogen bond to a surface oxygen atom [8]. In the FTIR study of ST-01 at 0.01 Pa, 80% of the intensity of the OH stretching band at room temperature was contributed by molecularly adsorbed water, while only 20% was by surface OH.…”
Section: Resultsmentioning
confidence: 99%
“…The surface hydroxyl group density of TiO 2 is considered to play a significant role in the photocatalytic processes [3,4,5]. Surface hydroxylated centers have been proposed to act as trapping sites for both electrons and holes migrated to the surface [6,7,8]. Several investigations have demonstrated that the additional hydroxyl groups on the TiO 2 surface can improve the adsorption capacity, the formation of mesoporous structure, and the catalytic efficiency [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…8 On the other hand, a recent study of photogenerated electron dynamics at the picosecond to nanosecond time scale shows that adsorbed water suppresses charge carrier recombination in anatase TiO 2 . 27,28 In order to evaluate whether adsorbed water has a positive or an adverse effect on the charge carrier recombination at the millisecond to minute time scale, we studied photogenerated electron absorption dynamics in the material which was dehydrated under dynamic vacuum ( p < 10 –3 mbar) at 623 K (sample iii). The room-temperature dark DRIFT spectrum of this sample is shown in Figure 1 (red curve).…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism is in accord with other relevant reports. [24] Water in the second layer weakens the interaction between first-layer water and TiO 2 ,t hus reducing the hole-trappingc apability. It has been found that hydrogen bondingw ith adsorbed water ontoa natase TiO 2 (1 01)s tabilizes surfacetrapped holes, lowers the barrier for hole migration (which enhances carrier mobility), and suppresses chargesrecombination on the timescale of minutes.…”
Section: Influence On the Dynamics Of The Photogenerated Chargesmentioning
confidence: 99%
“…[24,72] Blockingthese sites by surfacemodification statistically reduces subsequent interfacial electron transfer,s ot hat the most probablef ate of the charges is recombination. [24,72] Blockingthese sites by surfacemodification statistically reduces subsequent interfacial electron transfer,s ot hat the most probablef ate of the charges is recombination.…”
Section: Influence On the Dynamics Of Photogenerated Chargesmentioning
confidence: 99%